GaAsSbP QUASITERNARY MATERIAL SYSTEM: NANOSTRUCTURES GROWTH FEATURES AND IMMISCIBILITY ANALYSIS - K. M. Gambaryan; A. K. Simonyan; V. M. Aroutiounian
The continuum elasticity model is applied to quantitatively investigate the growth features and nucleation mechanism of quantum dots (QDs), nanopits, and coopetative QDs–nanopits structures in GaAsSbP quasiternary systems. We determine the critical lattice mismatch of GaAs/GaAsSbP system equal to when the growth mode changes from nucleation of QDs to formation of nanopits. We show that the island’s total energy and volume for that system are decreasing with increasing of the strain. The free energy of mixing for GaAs1xySbxPy quasiternary system is calculated and studied and its 3D sketch is plotted. It is demonstrated that there are some immiscibility gap for that system, which strongly depends on temperature.
Keywords: Physics; Materials science